Disulfiram inhibits liver fibrosis in rats by suppressing hepatic stellate cell activation and viability - Xiao-Mei Yang; Zheng Wu; Xiaoqi Wang; Yaoqi Zhou; Lei Zhu; Dongxue Li; Hui-Zhen Nie; Ya-Hui Wang; Jun Li; Xueyun Ma (BMC, 2022)
Abstract Background Liver fibrosis is a wound-healing response to chronic injury, featuring with excess accumulation of extracellular matrix secreted by the activated hepatic stellate cells (HSC). Disulfiram (DSF), also known as Antabuse, has been used for the treatment of alcohol addiction and substance abuse. Recently, overwhelming studies had revealed anti-cancer effects of DSF in multiple cancers, including liver cancer. But the actual effects of DSF on liver fibrosis and liver function remain unknown. Methods In this study, we evaluated the effects of low-dose DSF in CCl4- and Bile Duct Ligation (BDL)-induced hepatic fibrosis rat models. Cell proliferation was detected by using the Cell-Light™ EdU Apollo®567 Cell Tracking Kit. Cell apoptosis was analyzed using a TdT-mediated dUTP nick end labeling (TUNEL) kit, viability was measured with Cell Counting Kit-8(CCK8). Relative mRNA expression of pro-fibrogenic was assessed using quantitative RT-PCR. The degree of liver fibrosis, activated HSCs, were separately evaluated through Sirius Red-staining, immunohistochemistry and immunofluorescence. Serum alanine aminotransferase (ALT) and asparagine aminotransferase (AST) activities were detected with ALT and AST detecting kits using an automated analyzer. Results Liver fibrosis was distinctly attenuated while liver functions were moderately ameliorated in the DSF-treated group. Activation and proliferation of primary rat HSCs isolated from rat livers were significantly suppressed by low-dose DSF. DSF also inhibited the viability of in vitro cultured rat or human HSC cells dose-dependently but had no repressive role on human immortalized hepatocyte THLE-2 cells. Interestingly, upon DSF treatment, the viability of LX-2 cells co-cultured with THLE-2 was significantly inhibited, while that of THLE-2 co-cultured with LX-2 was increased. Further study indicated that HSCs apoptosis was increased in DSF/CCl4-treated liver samples. These data indicated that DSF has potent anti-fibrosis effects and protective effects toward hepatocytes and could possibly be repurposed as an anti-fibrosis drug in the clinic. Conclusions DSF attenuated ECM remodeling through suppressing the transformation of quiet HSCs into proliferative, fibrogenic myofibroblasts in hepatic fibrosis rat models. DSF provides a novel approach for the treatment of liver fibrosis.